Biodiversity and Distribution of Mushroom Coral (Fungiidae) in The Amurang Bay, South Minahasa - Hermanto, Bambang (Oseanologi dan Limnologi di Indonesia, 2017)
Mushroom coral is the one of sclerectinians that has essential role to form coral reefs. This kind of species act as a microhabitat for other marine organisms such as shrimp. cryptobenthic fish, barnacle and crab. Most of these unique species have an ability to move from one habitat to another during benthic phase. The aim of this research was to determine the community structure and distribution of mushroom corals. This research was conducted in February 2017 at 4 research stations using belt transect method withÂ  50x2m2 length of transects. The results showed that 431 individuals consisting of 19 species and 11 genus were recorded. Generally, the range of values of diversity index (H) was between 0,85-1,06Â  (low to medium level). The evennes index (J) values was ranged from 0,81 to 0,89 (high level) while the richness index (D) was 2,47-3,58 (low level). Lythophyllon repanda, Lythophyllon concinna and Fungia fungites were the most dominant mushroom coral spesies in the Amurang Bay waters.